« … qu’il prenne également soin de sa conduite ». Les fidéjusseurs dans la justice locale, Tlaxcala, 1822-1824 - Mirian Galante (Caravelle)
Based on the reconstruction of legal literature, but also on its application in civil and criminal justice in the region of Tlaxcala (1822-1824), this article proposes an analysis of fiadores (guarantors) as relevant actors in local conflicts’ resolution processes. These subjects represented socially respectable values (trustworthy) while allowing a more balanced functioning of justice mechanisms.